Welcome to Westonci.ca, your one-stop destination for finding answers to all your questions. Join our expert community now! Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To simplify the expression [tex]\(\log(9x^5) + 5 \log\left(\frac{1}{x}\right)\)[/tex], let's use the properties of logarithms step-by-step.
First, recall the logarithm properties:
1. [tex]\(\log(ab) = \log a + \log b\)[/tex]
2. [tex]\(\log\left(\frac{a}{b}\right) = \log a - \log b\)[/tex]
3. [tex]\(\log(a^b) = b \log a\)[/tex]
Given expression: [tex]\(\log(9x^5) + 5 \log\left(\frac{1}{x}\right)\)[/tex]
We will handle each part of the expression individually:
### Step 1: Simplify [tex]\(\log(9x^5)\)[/tex]
Using the property [tex]\(\log(ab) = \log a + \log b\)[/tex]:
[tex]\[ \log(9x^5) = \log 9 + \log x^5 \][/tex]
Then, using the property [tex]\(\log(a^b) = b \log a\)[/tex]:
[tex]\[ \log x^5 = 5 \log x \][/tex]
So,
[tex]\[ \log(9x^5) = \log 9 + 5 \log x \][/tex]
### Step 2: Simplify [tex]\(5 \log\left(\frac{1}{x}\right)\)[/tex]
Using the property [tex]\(\log \left(\frac{a}{b}\right) = \log a - \log b\)[/tex]:
[tex]\[ \log\left(\frac{1}{x}\right) = \log 1 - \log x \][/tex]
Since [tex]\(\log 1 = 0\)[/tex],
[tex]\[ \log\left(\frac{1}{x}\right) = -\log x \][/tex]
Then multiply by 5:
[tex]\[ 5 \log\left(\frac{1}{x}\right) = 5(-\log x) = -5 \log x \][/tex]
### Step 3: Combine the simplified parts
Now, combining the simplified parts from Step 1 and Step 2:
[tex]\[ \log(9x^5) + 5 \log\left(\frac{1}{x}\right) = (\log 9 + 5 \log x) + (-5 \log x) \][/tex]
Observe that [tex]\(5 \log x - 5 \log x\)[/tex] cancels out:
[tex]\[ \log(9x^5) + 5 \log\left(\frac{1}{x}\right) = \log 9 \][/tex]
### Conclusion:
Thus, the simplified form of [tex]\(\log(9x^5) + 5 \log\left(\frac{1}{x}\right)\)[/tex] is [tex]\(\log 9\)[/tex].
Hence, the correct answer is:
A. [tex]\(\log 9\)[/tex]
First, recall the logarithm properties:
1. [tex]\(\log(ab) = \log a + \log b\)[/tex]
2. [tex]\(\log\left(\frac{a}{b}\right) = \log a - \log b\)[/tex]
3. [tex]\(\log(a^b) = b \log a\)[/tex]
Given expression: [tex]\(\log(9x^5) + 5 \log\left(\frac{1}{x}\right)\)[/tex]
We will handle each part of the expression individually:
### Step 1: Simplify [tex]\(\log(9x^5)\)[/tex]
Using the property [tex]\(\log(ab) = \log a + \log b\)[/tex]:
[tex]\[ \log(9x^5) = \log 9 + \log x^5 \][/tex]
Then, using the property [tex]\(\log(a^b) = b \log a\)[/tex]:
[tex]\[ \log x^5 = 5 \log x \][/tex]
So,
[tex]\[ \log(9x^5) = \log 9 + 5 \log x \][/tex]
### Step 2: Simplify [tex]\(5 \log\left(\frac{1}{x}\right)\)[/tex]
Using the property [tex]\(\log \left(\frac{a}{b}\right) = \log a - \log b\)[/tex]:
[tex]\[ \log\left(\frac{1}{x}\right) = \log 1 - \log x \][/tex]
Since [tex]\(\log 1 = 0\)[/tex],
[tex]\[ \log\left(\frac{1}{x}\right) = -\log x \][/tex]
Then multiply by 5:
[tex]\[ 5 \log\left(\frac{1}{x}\right) = 5(-\log x) = -5 \log x \][/tex]
### Step 3: Combine the simplified parts
Now, combining the simplified parts from Step 1 and Step 2:
[tex]\[ \log(9x^5) + 5 \log\left(\frac{1}{x}\right) = (\log 9 + 5 \log x) + (-5 \log x) \][/tex]
Observe that [tex]\(5 \log x - 5 \log x\)[/tex] cancels out:
[tex]\[ \log(9x^5) + 5 \log\left(\frac{1}{x}\right) = \log 9 \][/tex]
### Conclusion:
Thus, the simplified form of [tex]\(\log(9x^5) + 5 \log\left(\frac{1}{x}\right)\)[/tex] is [tex]\(\log 9\)[/tex].
Hence, the correct answer is:
A. [tex]\(\log 9\)[/tex]
We hope our answers were helpful. Return anytime for more information and answers to any other questions you may have. We hope this was helpful. Please come back whenever you need more information or answers to your queries. We're glad you chose Westonci.ca. Revisit us for updated answers from our knowledgeable team.